¿Ingeniería política o una piuma al vento? El proyecto de justicia transicional en Argentina, 1982-1987 - Diego Galante (Nuevo mundo - Mundos Nuevos, 2017)
Since 1983, in Argentina, Alfonsin’s government developed a transitional justice program to prosecute human rights violations committed since 1976 to 1983. This paper reviews the intellectual and political history of that proposal, and analyzes the different changes introduced between 1983 and 1987. Looking into the program origins (1982), the early political statements and debates (1983-1984), the first trials that were conducted and the enactment of the “impunity laws” (1985-1987), the author finally concludes about the existence of a constitutive tension that was placed on the center of that processes.